Conditional Fictive Objects in Contemporary Sculpture Practice - Rajaa Paixão (Cadernos de Arte Pública)
This article presents an overview of a body of sculptural works developed for a practice-based research in Fine Arts. The research investigates contemporary sculpture as fictive object through subjectivity and its understanding in postmodernist theory, using real and imagined narratives as a catalyst. It adopts a reflective practice methodology to scrutinise the course of sculpture making when created under conditional spatiotemporal circumstances, with the primary objective of deepening the understanding of sculpture as (fictive) object and delineate its possible roles.